1981
DOI: 10.1111/j.1471-4159.1981.tb01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Arachidonoyl‐Labeled Phosphatidylinositols by Brain Synaptosomes

Abstract: Incubation of synaptosomes together with 1-acyl-2-[14C]arachidonoyl-sn-glycerophosphoinositols (GPI) and sodium deoxycholate yielded diacylglycerols and free arachidonic acid. Diacylglycerol formation is attributed to hydrolysis by the diacyl-GPI-specific phospholipase C (EC 3.1.4.10), and this reaction requires sodium deoxycholate for optimal activity. The free arachidonic acid formed is attributed to hydrolysis of diacyl-GPI by phospholipase A (EC 3.1.1.5). Free fatty acid release was observed during incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The high incorporation of arachidonic acid into phosphatidylinositol of mouse brain has been reported by Sun et al (1979). Der and Sun (1981) also reported the presence of a phospholipase C specific for phosphatidylinositol in brain synaptosomes.…”
Section: Discussionmentioning
confidence: 60%
“…The high incorporation of arachidonic acid into phosphatidylinositol of mouse brain has been reported by Sun et al (1979). Der and Sun (1981) also reported the presence of a phospholipase C specific for phosphatidylinositol in brain synaptosomes.…”
Section: Discussionmentioning
confidence: 60%
“…Phosphatidylinositol (PI)-specific phospholipase C has found widespread use in the solubilization of membrane-bound enzymes [4][5][6]. Moreover, sodium deoxycholate (DOC) activated the endogenous PI-specific phospholipase C in the brain and platelets [7][8][9]. Here we show that PIspecific phospholipase C of S. aureus or DOC-activated endogenous phospholipase C solubilizes AChE and AAA of sheep brain basal ganglia and that beyond a critical [DOC], a loss in activity of these enzymes occurs which can be restored by externally added PI.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphatidylinositol can also be metabolised by lysosomal enzymes, which consist of both a Ca2 +-independent phosphodiesterase and phospholipase-A-type enzymes which bring about a complete deacylation of the phospholipid to glycerophosphoinositol [12, 131. Recently, Shum et al [I41 have reported that the deacylation of phosphatidylinositol by phospholipase A, and A, may occur in a rat brain microsomal fraction as measured by the release of the fatty acids from phosphatidylinositol in the presence of 5 mM CaCI,. It has also been reported that a phospholipase A (most likely A,) active against phosphatidyl- inositol exists in mouse brain synaptosomes [15]. Finally, when phosphatidylinositol was incubated with a soluble extract from rat brain, a small amount of free fatty acid was released although the major products were phosphoinositol and diacylglycerol [3].…”
mentioning
confidence: 99%